Spatiotemporal Estimation of the Potential Adoption of Photovoltaic Systems on Urban Residential Roofs - Mejia, Mario A. [UNESP]; Macedo, Leonardo H. [UNESP]; Pinto, Tiago; Franco, John F. [UNESP] (MDPI, 2024)
The adoption of residential photovoltaic (PV) systems to mitigate the effects of climate change has been incentivized in recent years by government policies. Due to the impacts of these systems on the energy mix and the electrical grid, it is essential to understand how these technologies will expand in urban areas. To fulfill that need, this article presents an innovative method for modeling the diffusion of residential PV systems in urban environments that employs spatial analysis and urban characteristics to identify residences at the subarea level with the potential for installing PV systems, along with temporal analysis to project the adoption growth of these systems over time. This approach integrates urban characteristics such as population density, socioeconomic data, public environmental awareness, rooftop space availability, and population interest in new technologies. Results for the diffusion of PV systems in a Brazilian city are compared with real adoption data. The results are presented in thematic maps showing the spatiotemporal distribution of potential adopters of PV systems. This information is essential for creating efficient decarbonization plans because, while many households can afford these systems, interest in new technologies and knowledge of the benefits of clean energy are also necessary for their adoption.
Keywords: energy transition; geographical information systems; geographically weighted regression; logistics growth model; moving average; residential photovoltaic systems; spatiotemporal estimation